Report from the Select Committee, to whom it was referred to consider and examine the accounts of extraordinary services incurred and paid, and not provided for by Parliament : which have been laid before the House of Commons in the years 1776, 1777, and 1778. (Making of the modern world (Goldsmiths'-Kress Library of Economic Literature), 1778)
Rum rations for the British army.